2016
DOI: 10.1111/geoa.12132
|View full text |Cite
|
Sign up to set email alerts
|

Sediments from around the lower younger dryas boundary (se arizona, usa): implications from la‐icp‐ms multi‐element analysis

Abstract: One of the prominent features in sediment sequences formed around the Allerød‐Younger Dryas transition (c. 12.9–12.8 ka bp) in North America is a dark layer of organic‐rich material, i.e. the black mat. The black mat sequences in southeast Arizona contain a thin sandy basal layer corresponding to the lower Younger Dryas boundary. Trace element concentrations in the lower Younger Dryas boundary sediments, in the black mat, in the host sediments, and in charcoal from Western Europe and southeast Arizona were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In 2013, Petaev et al reported the discovery of a distinct peak concentration in Pt in the GISP2 core of Greenland in the YD peak, which they attributed to material deposited by a Pt-rich impactor. Subsequently Pt enrichment well above background levels in YDB sediments have been reported at 28 sites across North America, Europe, and Asia by Moore et al (2017) and Gramly et al (2017); Andronikov and Andronikova (2016) and Andronikov et al (2011, 2014, 2015, 2016b, 2016c) also reported peak concentrations of Ir in the YDB layer at multiple sites in North America and Europe.…”
Section: Iridium and Platinum And Their Interpretationmentioning
confidence: 70%
“…In 2013, Petaev et al reported the discovery of a distinct peak concentration in Pt in the GISP2 core of Greenland in the YD peak, which they attributed to material deposited by a Pt-rich impactor. Subsequently Pt enrichment well above background levels in YDB sediments have been reported at 28 sites across North America, Europe, and Asia by Moore et al (2017) and Gramly et al (2017); Andronikov and Andronikova (2016) and Andronikov et al (2011, 2014, 2015, 2016b, 2016c) also reported peak concentrations of Ir in the YDB layer at multiple sites in North America and Europe.…”
Section: Iridium and Platinum And Their Interpretationmentioning
confidence: 70%
“…Their results indicate that extraterrestrial Pt settled out of the atmosphere into a 21-y interval of ice, rising 100 times above background at 12,822 5 140 cal BP, within the range 12,836-12,815 cal BP. Including this discovery, there have been multiple independent reports of Pt abundance peaks in the YDB layer at 22 sites in North America, Europe, and Asia: one site in Greenland (Petaev et al 2013b), one site in Russia (Andronikov et al 2014), four sites in Lithuania (Andronikov et al 2015), one site on the French-Italian border (Mahaney et al 2016b), two sites in the Netherlands (Andronikov et al 2016b), one site in Belgium (Andronikov et al 2016b), and 12 sites in the United States (Andronikov and Andronikova 2016;Moore et al 2017).…”
Section: Resultsmentioning
confidence: 97%
“…The existence of such an impact proxy at the YD onset was predicted for Greenland ice core records at the time the YDB hypothesis was first proposed 1 . Since that initial discovery of a YDB Pt peak in Greenland, several more investigations have found elevated concentrations of Pt, and other Pt-group elements (PGEs), and high-temperature PGE-rich spherules, marking the YD onset within 28 widely separated sediment sequences across North America, Europe, and Asia 45 , 47 , 61 64 (Fig. 12 ).…”
Section: Resultsmentioning
confidence: 99%